Pemberdayaan Budaya Lokal dalam Pengelolaan Rumah Topeng dan Wayang Setia Darma - Intan Saptiari, Ni Luh Made; Nugroho, Wahyu Budi; Krisna Aditya, I Gst. Ngr. Agung (JURNAL ILMIAH SOSIOLOGI (SOROT), 2021)
ABSTRACT This study analyzes how the role of the Setia Darma House of Mask and Puppets as an information center to preserve and maintain the traditional arts of local culture. The method used in this research is quaIitative with an explanative descriptive type. The theory used is the local cultural empowerment theory from Jim Ife. This theory explains how the empowerment of local culture is an important part and component in instilling a sense of community to appreciate and maintain the preservation of local culture. From the analysis carried out, there were various positions conveyed by the informants. Most of the informations revealed that changes by presering and maintaining local cultural arts.The owner is sentral to empowering the Balinese dan Indonesia culture. The empowerment of local culture has been carried out to create changes towards the better so that traditional arts are more appreciated by the wider community. Keywords: Local Culture Empowerment, Management, Appreciation, Culture